The age of Churchill and Eden : 1940 - 1957 - Ramsden, John (A history of the Conservative Party;, 1995)
In this book, Dr. Ramsden recounts the Conservatives' eclipse during the latter part of the Second World War, and explains the Party's crushing defeat in the postwar election of 1945. He reassesses the Tory recovery under the guidance of R. A. Butler and Lord Woolton in the later 1940s, and throws new light on how that recovery was achieved. He discusses the Party's stormy relationship with Churchill, and the efforts of other Conservatives to make him retire. He evaluates the career of Sir Anthony Eden, and the Suez crisis which ended it; and he charts the rise to the premiership of Harold Macmillan. The Age of Churchill and Eden has been written with full access to the Conservative Party's archives, both nationally (including Conservative Central Office, the Party Whips and the Research Department) and locally (the minute books of area and constituency parties).